The effect of the use of special exercises directed towards Sensory perception of motor to improve the skill of receiving the serve in volleyball - Zahra, Mayssem; Salama, Luay; Al – Halabi, Mohammed (Latakia University Journal -Medical Sciences Series, 2018)
The improvement and development of sports performance has been and remains a goal pursued by every coach and player. With the development of the great mathematical sciences and the results that have been achieved now, new means and methods of education and training have emerged more useful and effective compared to the old methods used. However, many trainers and teachers They still rely on classical old concepts and methods while working in the education and training of sports skills. That the lack of use of research results and theories of new science may affect the mastery of the individual athlete of these skills in the best way, which called for the current study, which focused on the cognitive field, by proposing organized and targeted exercises, to develop sense of movement by easy and simplified means, to improve the performance of skill. The skill of receiving volleyball was chosen because of its importance, the scarcity of use in previous studies and the fact that it is considered to be the basic and important skills in this game. The sample consisted of (22) students of the second year in the Faculty of Physical Education, Tishreen University, and the experimental method was used in the style of the two groups (control - experimental). The experimental group underwent regular exercises, in addition to special exercises aimed at sensory perception. The control group was only subjected to normal exercises. Compared to the remote tests between the experimental and control groups, the results showed that there was a positive effect on the use of sensory. According to the results of the study, it was recommended that workers in the field of volleyball education and training should pay attention to the cognitive aspect, through the development of targeted exercises for the development of the sense of movement during the education and training of sports skills, for their effective role in obtaining better results. اثر استخدام تمرينات خاصة وموجهة للإدراك الحس حركي على تحسين مهارة استقبال الارسال بالكرة الطائرة إنَّ تحسينَ وتطويرَ مستوى الأداء الرياضي كان وما زال هدفٌ يسعى لتحقيقه كلُّ مدرب ولاعب، وفي ظل تطوّر العلوم الرياضية الكبير، والنتائج التي توصلت إليها الآن, ظهرت وسائل وأساليب حديثة في التعليم والتدريب أكثر فائدة وفعالية مقارنةً بالوسائل القديمة المستخدمة، غير أن كثيراً من المدربين والمعلمين مازالوا يعتمدون على مفاهيم وأساليب قديمة كلاسيكية أثناء عملهم في تعليم وتدريب المهارات الرياضية. أن عدمَ استخدام نتائج الأبحاث ونظريات العلوم الجديدة قد يؤثر على اتقان الفرد الرياضي لهذه المهارات بالشكل الأمثل, هذا ما دعا إلى الدراسة الحالية, التي تركَّزت على المجال الإدراكي، وذلك باقتراح تمرينات منظمة وهادفة, لتنمية الإدراك الحس حركي بوسائل سهلة ومبسطة, لتحسين الأداء المهاري. وقد تمّ اختيار مهارة استقبال الإرسال بالكرة الطائرة نظراً لأهميتها، وندرة استخدامها في الدراسات السابقة وكونها تعتبر من المهارات الأساسية والمهمّة في هذه اللعبة. وتكونت العينة من (22) طالب من السنة الثانية في كلية التربية الرياضية بجامعة تشرين، وتمّ استخدام المنهج التجريبي بأسلوب المجموعتين المتكافئتين (الضابطة - التجريبية). خضعت المجموعة التجريبية لتمرينات اعتيادية، إضافةً لتمرينات خاصة موجهة للإدراك الحس حركي أمّا المجموعة الضابطة، فخضعت فقط للتمرينات الاعتيادية، وبالمقارنة بالاختبارات البعدية بين المجموعتين التجريبية والضابطة، أظهرت نتائج الدراسة أن هناك أثرٌ إيجابي لاستخدام تمريناتٍ موجَّهةٍ للإدراك الحس حركي على تحسين مهارة استقبال الإرسال للمجموعة التجريبية. ووفقاً لنتائج الدراسة، تمّت التوصية للعاملين في مجال التعليم والتدريب بالكرة الطائرة على ضرورة الاهتمام بالجانب الإدراكي, من خلال وضعِ تمرينات موجهة لتنمية الإدراك الحس حركي أثناء تعليم وتدريب المهارات الرياضية, ذلك لدورها الفاعل في الحصول على نتائج أفضل.